Fit to run the complete guide to injury-free running - Pearson, Philip (The Crowood Press Ltd, 2014)
Running remains one of the cheapest and most accessible forms of aerobic fitness; all you need is a pair of running shoes and the courage to step out of the front door. Aimed at everyone from the complete beginner to the experienced club runner, Pearson covers it all: warm-up and cool-down; stretching exercises; technique; core stability and posture; diet and nutrition; treating injuries, and an introduction to current exercise science